Nine new species of black lichenicolous fungi from the genus Cladophialophora (Chaetothyriales) from two different climatic zones of China - Chang, Runlei; Wang, Yichen; Liu, Yanyu; Wang, Yiran; Li, Shiguo; Zhao, Guoyan; Zhang, Susu; Dai, Meixue; Zheng, Xiaoxiao; Bose, Tanay; Si, Hongli (Frontiers in Microbiology, 2023)
Lichenicolous fungi are parasites of lichens. Many of these fungi are referred to as ‘black fungi’. A diversity of these black fungi include species that are pathogenic to humans and plants. A majority of black fungi reside in the phylum Ascomycota within the sub-classes Chaetothyriomycetidae and Dothideomycetidae. To explore the diversity of lichenicolous ‘black fungi’ associated with lichens in China, we conducted several field surveys in the Inner Mongolia Autonomous Region and Yunnan Province between 2019 and 2020. We recovered 1587 fungal isolates from the lichens collected during these surveys. During the preliminary identification of these isolates using the complete internal transcribed spacer (ITS), partial large subunit of nuclear ribosomal RNA gene (LSU), and small subunit of nuclear ribosomal RNA gene (SSU), we identified 15 fungal isolates from the genus Cladophialophora. However, these isolates had low sequence similarities with all known species from the genus. Therefore, we amplified additional gene regions, such as, translation elongation factor (TEF) and partial β-tubulin gene (TUB), and constructed a multi-gene phylogeny using maximum likelihood, maximum parsimony, and Bayesian inference. In our datasets, we included type sequences where available for all Cladophialophora species. Phylogenetic analyses revealed that none of the 15 isolates belonged to any of the previously described species in the genus. Therefore, using both morphological and molecular data, we classified these 15 isolates as nine new species within the genus Cladophialophora: C. flavoparmeliae, C. guttulate, C. heterodermiae, C. holosericea, C. lichenis, C. moniliformis, C. mongoliae, C. olivacea, and C. yunnanensis. The outcome from this study shows that lichens are an important refugia for black lichenicolous fungi, such as those from Chaetothyriales.